ECOSYSTEM SERVICES AS A BASIS FOR CLIMATE ADAPTATION INDICATORS: A CASE FROM URBAN INDIA - Naaz, Shaila; Mehrotra, Nirmita (International Journal of Engineering Technologies and Management Research, 2025)
Climate change poses significant threats to urban sustainability, particularly in rapidly growing cities where ecological degradation amplifies vulnerability to extreme weather events. Ecosystem services (ES)—the benefits derived from natural systems—offer a vital framework for developing climate adaptation strategies by linking ecological functions with human well-being. This study explores how ecosystem services can serve as a basis for identifying and evaluating climate adaptation indicators. Through an integrative review of literature and case-based analysis, the research highlights the role of provisioning, regulating, cultural, and supporting services in enhancing adaptive capacity. The final set of indicators was established following a comprehensive data collection process involving surveys and questionnaires administered to key stakeholders. These stakeholders comprised professionals from relevant fields, specifically urban planners, policy makers, architects, urbanists, urban designers, urban foresters, and individuals engaged in the urban infrastructure sector." Indicators such as urban green cover, water retention potential, biodiversity index, carbon sequestration, and social access to green infrastructure are identified as measurable parameters for adaptation assessment. The findings emphasize that embedding ecosystem service-based indicators within urban planning can improve resilience, promote sustainable land-use management, and support evidence-based policy formulation. By positioning ecosystem services at the core of adaptation frameworks, cities can transition from reactive to proactive climate governance that synergizes ecological health with socio-economic sustainability.